Dynamic Modeling and Simulation Control of 3-DOF Bionic Shoulder Joint - Li Fang; Xu Jiaqi; Liu Kai; Wu Yang (Jixie chuandong)
According to the characteristics of shoulder joint,a decoupling parallel bionic shoulder joint driven by pneumatic muscle actuators（ PMAs） is presented. Based on screw theory,the freedoms of 3-DOF parallel mechanism are analyzed. The kinematics model of parallel mechanism is established because of its simple reverse solution. Besides,its dynamics model is also established based on Lagrange method. In simulation control,computed torque method can better control motion of parallel mechanism,which verifies the correctness of the dynamic model at the same time.